Regional inequality in decentralized countries: a multi-country analysis using LIS - Javier Martín-Román; Luis Ayala; Juan Vicente (Luxembourg Income Study (LIS), 2017)
The aim of this paper is to analyze the regional disparities of six decentralized countries using LIS microdata. In order to determine the extent of the territorial variable in the explanation of income inequality, we carry out two complementary analyses. On the one hand, we perform the classical decomposition by population subgroups of different inequality measures. On the other hand, we implement a semiparametric decomposition analysis based on the method proposed by DiNardo, Fortin and Lemieux.
Keywords: D31; D33; R23; 330; income inequality; regional inequality; subgroup decomposition; semiparametric decomposition